Biodegradable glycopolymer-b-poly(ε-caprolactone) block copolymer micelles: versatile construction, tailored lactose functionality, and hepatoma-targeted drug delivery1. Issue 11 (21st March 2015) - Chen, Wei; Meng, Fenghua; Cheng, Ru; Deng, Chao; Feijen, Jan; Zhong, Zhiyuan
<x xml:space="preserve">Abstract</x> An illustration of versatile construction of biodegradable glycopolymer-PCL micelles with tailored LBA-functionality for hepatoma-targeted drug delivery.